2014
DOI: 10.1021/la503439g
|View full text |Cite
|
Sign up to set email alerts
|

Succinimidyl Ester Surface Chemistry: Implications of the Competition between Aminolysis and Hydrolysis on Covalent Protein Immobilization

Abstract: N-Hydroxysuccinimide (NHS) ester terminal groups are commonly used to covalently couple amine-containing biomolecules (e.g., proteins and peptides) to surfaces via amide linkages. This one-step aminolysis is often performed in buffered aqueous solutions near physiological pH (pH 6 to pH 9). Under these conditions, the hydrolysis of the ester group competes with the amidization process, potentially degrading the efficiency of the coupling chemistry. The work herein examines the efficiency of covalent protein im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
120
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(124 citation statements)
references
References 64 publications
(127 reference statements)
4
120
0
Order By: Relevance
“…It was reported that similar to alkanethiols, disulfides are adsorbed on the gold surface spontaneously upon cleavage of the S‐S bond due to the reductive property of gold, resulting in the Au‐S bond formation. Complementary with these findings, S 2p spectra of DSP, NHSS and NHS derivative (disulfide containing molecules of similar structure) modified surfaces demonstrate the spontaneous cleavage of the S‐S bond and covalent attachment of these molecules through gold thiol (Au‐S) interactions without any treatment with reducing agents . The S 2p spectra of all the samples are shown in Figure .…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…It was reported that similar to alkanethiols, disulfides are adsorbed on the gold surface spontaneously upon cleavage of the S‐S bond due to the reductive property of gold, resulting in the Au‐S bond formation. Complementary with these findings, S 2p spectra of DSP, NHSS and NHS derivative (disulfide containing molecules of similar structure) modified surfaces demonstrate the spontaneous cleavage of the S‐S bond and covalent attachment of these molecules through gold thiol (Au‐S) interactions without any treatment with reducing agents . The S 2p spectra of all the samples are shown in Figure .…”
Section: Resultsmentioning
confidence: 88%
“…All the O 1 s spectra have the characteristic oxygen peak around 532.0 eV which is partially attributed to environmental oxygen (Figure A). However, Lim et al, defined the peak at 532.1 eV as the C=O functional group of the DSP molecule . In addition, this group identified another peak at 534.4 eV, which corresponds to NHS ester oxygen.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…These components were assigned to imide and thiadiazole groups and protonated imide group, respectively. [9,10] Also the XPS investigation of silane (Fig. 3d) revealed the presence of two components in the N 1s spectrum, localized at BE = 399.6 eV (1′′′) and 401.6 eV (2′′′) and assigned to amide or amine and protonated amide or amine groups, respectively.…”
Section: Resultsmentioning
confidence: 97%
“…Most importantly, the coupling reaction is often performed in buffered aqueous solutions near physiological pH (pH 6 to pH 9). Under these conditions, the hydrolysis of the ester group competes with the amidization process, potentially degrading the efficiency of the coupling chemistry20 . Last but not least, the reaction between active esters and amino groups is notregiospecific and does not allow the controlled and oriented immobilization of the protein.…”
mentioning
confidence: 99%